The Fibrin Cleavage Product Bβ15-42 Channels Endothelial and Tubular Regeneration in the Post-acute Course During Murine Renal Ischemia Reperfusion Injury - Fischer, Dania; Seifen, Christopher; Baer, Patrick; Jung, Michaela; Mertens, Christina; Scheller, Bertram; Zacharowski, Kai; Hofmann, Rainer; Maier, Thorsten J.; Urbschat, Anja (Frontiers in Pharmacology, 2018)
Early and adequate restoration of endothelial and tubular renal function is a substantial step during regeneration after ischemia reperfusion (IR) injury, occurring e.g. in kidney transplantation, renal surgery, and sepsis. While tubular epithelial cell injury has long been of central importance, recent perception includes the renal vascular endothelium. In this regard, the fibrin cleavage product fibrinopeptide Bβ15-42 mitigate IR injury by stabilizing interendothelial junctions through its affinity to VE-cadherin. Therefore, this study focused on the effect of Bβ15-42 on post-acute physiological renal regeneration. For this, adult male C57BL/6 mice were exposed to a 30 min. bilateral renal ischemia and reperfusion for 24h and 48h. Animals were randomized in a non-operative control group, two operative groups each treated with i.v. administration of either saline or Bβ15-42 (2.4 mg/kg) immediately prior to reperfusion. Endothelial activation and inflammatory response was attenuated in renal tissue homogenates by single application of Bβ15-42. Meanwhile, Bβ15-42 did not affect acute kidney injury markers. Regarding the angiogenetic players VEGF-A, Angiopoietin-1, Angiopoietin-2, however, we observed significant higher expressions at mRNA and trend to higher protein level in Bβ15-42 treated mice, compared to saline treated mice after 48h of IR, thus pointing towards an increased angiogenetic activity. Similar dynamics were observed for the intermediate filament vimentin, the cytoprotective protein klotho, stathmin and the proliferation cellular nuclear antigen (PCNA), which were significantly up-regulated at the same points in time. These results suggest a beneficial effect of anatomical contiguously located endothelial cells on tubular regeneration through stabilization of endothelial integrity. Therefore, it seems that Bβ15-42 represents a novel pharmacological approach in the targeted therapy of acute renal failure in everyday clinical practice.